Petrology of the high-Mg tonalites and dioritic enclaves of the ca. 2130Ma Alto Maranhão suite: evidence for a major juvenile crustal addition event during the Rhyacian orogenesis, Mineiro Belt, southeast Brazil. - Seixas, Luís Antônio Rosa (2014)
Combined field observations, petrography, mineral chemistry, geochemistry, Nd isotopes and U–Pb zir-con data are presented for the ca. 2130 Ma Alto Maranhão suite. The suite, composed by allanite-bearingbiotite hornblende tonalites and commingled dioritic mafic magmatic enclaves (MME), occupies an esti-mated area of >300 km2in the southern Quadrilátero Ferrífero region, Minas Gerais, Brazil. Tonalitesand commingled MME are medium-K rocks, with high-Mg (Mg-number ≥ 0.46) and high-Cr (≥55 ppm)contents. They are also enriched in large-ion lithophile elements (LILE, Sr, Ba), some high-field-strengthelements (HFSE, Th, U), and light rare earth elements (REE), but depleted in Nb, Ta, and heavy REE. TDMmodel ages for tonalites and MME are similar and range from 2.3 to 2.4 Ga. The εNd(t) values are groupedaround chondritic values (=0 ± 1.0). Field relations and geochemical data indicate that tonalites and com-mingled dioritic MME crystallized as synchronous independent magma pulses, with limited mixing. Bothmagmas are compositionally equivalent to high-Mg andesites in modern subduction zones, implying thatthe suite was issued from the partial melting of a mantle wedge metasomatised to different degrees byslab-derived melts. Geobarometry (aluminium-in-hornblende) indicates crystallization at mid-crustaldepths (i.e. 0.59–0.42 GPa). The igneous suite evolved by fractional crystallization of hornblende, biotiteand accessory minerals (zircon, apatite, allanite and Fe–Ti oxide). The ubiquitous occurrence of horn-blende and allanite in tonalites and dioritic MME suggests that this mineral pair was largely responsiblefor the observed changes of light REE/heavy REE and Eu/Eu* ratios within the members of the suite. Thegeographical extent (>1000 km2) and Paleoproterozoic ages of the Alto Maranhão suite (ca. 2130 Ma) andassociated granitoids of the Mineiro Belt (2.1–2.2 Ga) constitute a major event of juvenile addition to thecontinental crust in the context of the southern São Francisco craton, and the ca. 2.2–2.1 Ga Rhyacianorogenesis of the South American platform. The age and general geochemical characteristics of the AltoMaranhão suite and its emplacement after a ca. 2.35 Ga juvenile, tholeiitic-source derived high-Al TTGsuite, indicate a tectonic setting akin to that of Late-Archaean high-Mg granitoids.